2011
DOI: 10.1038/npp.2011.144
|View full text |Cite
|
Sign up to set email alerts
|

Haloperidol Regulates the State of Phosphorylation of Ribosomal Protein S6 via Activation of PKA and Phosphorylation of DARPP-32

Abstract: Administration of typical antipsychotic drugs, such as haloperidol, promotes cAMP-dependent signaling in the medium spiny neurons (MSNs) of the striatum. In this study, we have examined the effect of haloperidol on the state of phosphorylation of the ribosomal protein S6 (rpS6), a component of the small 40S ribosomal subunit. We found that haloperidol increases the phosphorylation of rpS6 at the dual site Ser235/236, which is involved in the regulation of mRNA translation. This effect was exerted in the MSNs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
64
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 49 publications
(67 reference statements)
9
64
2
Order By: Relevance
“…Our data strongly suggest that the partial ERKdependent phosphorylation of rpS6 previously observed (Gangarossa et al, 2011) is likely to occur through p90RSK since SKF81297 induces ERK-dependent phosphorylation of p90RSK while a decrease of p70S6K phosphorylation at Thr421/Ser424 is observed. Of interest, PKA and PKC have also been proposed to regulate rpS6 phosphorylation at Ser235/236 (Moore et al, 2009;Parker et al, 1985;Valjent et al, 2011). The present results show that inhibition of PKC prevents SKF81297 induced increase in rpS6 Ser235/236 phosphorylated site indicating a pivotal role of this kinase in this phenomenon.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Our data strongly suggest that the partial ERKdependent phosphorylation of rpS6 previously observed (Gangarossa et al, 2011) is likely to occur through p90RSK since SKF81297 induces ERK-dependent phosphorylation of p90RSK while a decrease of p70S6K phosphorylation at Thr421/Ser424 is observed. Of interest, PKA and PKC have also been proposed to regulate rpS6 phosphorylation at Ser235/236 (Moore et al, 2009;Parker et al, 1985;Valjent et al, 2011). The present results show that inhibition of PKC prevents SKF81297 induced increase in rpS6 Ser235/236 phosphorylated site indicating a pivotal role of this kinase in this phenomenon.…”
Section: Discussionsupporting
confidence: 51%
“…Phosphorylation of rpS6 on this residue is known to correlate with an increase in translation of specific mRNAs that contain an oligopyrimidine tract in their 5 0 UTR regions (Ruvinsky and Meyuhas, 2006). Interestingly, rpS6 protein, which possesses additional phosphorylation sites such as Ser240/244, can be phosphorylated by several kinases including 40S ribosomal protein S6 kinases (p70S6K) (Ruvinsky and Meyuhas, 2006), 90 kDa ribosomal S6 kinases (RSKs) (Roux et al, 2007) cAMP-dependent protein kinase (PKA) (Moore et al, 2009;Valjent et al, 2011) as well as protein kinase C (PKC) (Parker et al, 1985). In this study, we show that SKF81297 increases the phosphorylation of rpS6 at Ser235/236 but not at Ser240/244.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas DBA/2J mice showed no response to risperidone, high levels of phospho-Ser235/236-rpS6 were found in the striatopallidal pathway of the susceptible strain after drug treatment. In line with these observations, haloperidol has been associated with rpS6 phosphorylation at Ser235/236, specifically at the level of DRD2 MSN cells in the indirect striatopallidal pathway [40]. Recently, Dadalko et al [16] demonstrated the involvement of mTORC2 signaling in the regulation of the striatal dopamine (DA) tone and D2R signaling.…”
Section: Discussionmentioning
confidence: 50%
“…The partial reduction of histone H3 phosphorylation observed in MSK1 null mice indicates that additional kinases participate to chromatin modifications in response to L-DOPA. For instance, cAMP-dependent protein kinase (PKA) has been proposed to regulate Ser10 phosphorylation in response to administration of antipsychotic drugs (44, 45). …”
Section: Discussionmentioning
confidence: 99%